Rehabilitation of the knee following ACL repair and reconstruction: A review of clinical best practices - Haidar, Muhammad Daffa; Mulyawan, Rizki; Dewantara, Julian; Jurek, Joanna Michalina (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. ACL reconstruction is the surgical replacement of the anterior cruciate ligament with a tissue graft to restore knee function. To avoid problems including edema, loss of range of motion, muscle weakness, poor balance, and recovery of knee function, rehabilitation treatment should be performed after surgery. Immediate implementation of open kinetic chain exercises, use of criterion-based progressions for various activities such as running, sprinting, and plyometrics, and implementation of a secondary prevention program. This clinical practice review is to discuss the parameters associated with the rate of phase repair for ACL repair and to guide therapists according to the parameters of postoperative healing.Material and Methods. The patient presented with a knee brace still in place, swelling and incision marks above the patella, and atrophy of the dextra quadrisep muscle, the patient still had difficulty bending and straightening his right knee, and used crutches to help him walk. The modalities given are massage, electrotherapy (TENS), various exercises (exercise therapy), stretching, and cryotherapy.Results. There are five phases of rehabilitation: maximal protection, moderate protection, minimum protection (initial strengthening), Neuromuscular Control and Functional Training (strengthening-cardiovascular conditioning), and maintenance and Return to Activity (controlled agility-advanced conditioning). These stages are to help reduce swelling, increase joint range of motion, increase muscle strength, and reduce pain.Conclusion. Periodization theory should be fundamentally understood by sports rehabilitation professionals, especially physical therapists and sports medicine physicians. So that a safe and organized postoperative procedure can be established.